Reforming Ethical Oversight Mechanisms for Constitutional Court Justices in Indonesia - Citra Dewi Rahmah; Tunggul Anshari Setia Negara; Ngesti Dwi Prasetyo (Правові горизонти, 2025)
Relevance. The integrity of the Constitutional Court of Indonesia, as one of the judicial authorities in the post-reform constitutional system, demands not only independence but also ethical accountability of its justices. While Article 24 of the 1945 Constitution and Law No. 48 of 2009 safeguard judicial independence, oversight mechanisms particularly ethical ones remain limited and internally controlled. The abolition of the Constitutional Court Honorary Council of Appeals (Majelis Kehormatan Banding) and the lack of external checks have raised critical questions about due process, institutional legitimacy, and legal certainty in judicial ethical enforcement.